Effect of tool path and feed rate on the machining of coons surfaces / Boppana V. Chowdary and Anton Gittens - Boppana V. Chowdary; Anton Gittens (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In this study, complex shapes are defined as the sculptured surfaces created by the blending of curves, to form surface patches. Past investigations show that non-uniform rational B-Splines (NURBS) curves are the most appropriate for the modeling of sculptured surfaces. The main objective of this research is to examine the effects of toolpath and feed rate variations on the machining of the Coons surface, which is modeled through NURBS. Based on simulation results, it is clear that toolpath and feed rate selection plays a significant role in sculptured surface machining. In particular, the toolpath selection seemed to have a greater effect on the surface finish and machining time than the feed rate. The results also show that the feed rate option has a much greater effect on roughing than finishing operations. It can also be seen in this research that the toolpath option played a more significant role than feed rate selection in determining the file size.